Cholinergic neurons mediate CaMKII-dependent enhancement of courtship suppression. - Mehren, J.E.; Griffith, L.C. (Learning and Memory, 2006)
In Drosophila, calcium/calmodulin-dependent protein kinase II (CaMKII) activity is crucial in associative courtship conditioning for both memory formation and suppression of courtship during training with a mated female. We have previously shown that increasing levels of constitutively active CaMKII, but not calcium-dependent CaMKII, in a subset of neurons can decrease the initial level of courtship and enhance the rate of suppression of courtship in response to a mated female. In this study, we demonstrate that a subpopulation of noncholinergic, nondopaminergic, non-GABAergic neurons can cause CaMKII-dependent reductions in initial courtship, but only cholinergic neurons enhance training-dependent suppression. These data suggest that processing of pheromonal signals in two subpopulations of neurons, likely antennal lobe projection neurons, is critical for behavioral plasticity.